Benign subcutaneous emphysema: A case report with bite. (2015) - Onwochei, V.E.; Kelly, M.E.; Lyons, R.; Khan, W.; Barry, K.M.
Highlights: Benign subcutaneous emphysema is rare. Important to differentiate from life-threatening skin infections. Numerous causative factors. Medical management is not always effective (especially immunocompromised). May required surgical debridement for resolution of symptoms. Abstract: Introduction: Subcutaneous emphysema is the presence of air/gas within the subcutaneous tissue plane. Though there are numerous causative factors, benign subcutaneous emphysema is rare. Case report: We report a very rare case of benign subcutaneous emphysema following an insect bite on the forearm of a 48-year old man. The puncture area was erythematous and the emphysema extended to the whole arm, axilla and superior mediastinum. Despite, conservative management, the patient had residual discomfort and erythema around the puncture site. Surgical debridement resulted in resolution of symptoms. Discussion: Subcutaneous emphysema affecting an isolated limb is extremely rare. It is vital to differentiate it from life-threatening soft-tissue infections secondary to a gas-forming organism. Immunodeficiency states are key factors in the development and the outcomes of patients with subcutaneous emphysema. Medical management successfully resolves symptoms in the majority of cases. However, surgical debridement of the puncture site and surrounding fibrotic tissue has been advocated for those with persistent symptoms. Conclusion: This case highlights a rare cause of benign subcutaneous emphysema, highlighting key issues surrounding its management for a successful outcome.